2015
DOI: 10.3382/ps/pev166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different wavelengths of light on the biology, behavior, and production of grow-out Pekin ducks

Abstract: Previous research has shown that red light conditions may improve growth and decrease aggressive behaviors in chickens and turkeys; however, more recent studies suggest that blue-green light may improve production of broilers over red light. To date, no research has been conducted to examine whether different wavelengths of light have an impact on production in the Pekin duck. To determine this, we raised Pekin ducks under aviary conditions that were similar to standard commercial barns. The ducks were kept in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…The purpose of preening is to maintain feather quality and cleanliness in healthy birds. Our laboratory has examined and published observations of nearly 1,000,000 ducks raised with pin-metered water line systems; ducks observed in all our publications showed excellent body condition, particularly with eye and feather quality, and feather cleanliness regardless of other differences in management or environmental conditions (Fraley et al, 2013 ; Karcher et al, 2013 ; Campbell et al, 2014 ; Colton and Fraley, 2014 ; Rice et al, 2014 ; Campbell et al, 2015 ). Thus, we have not observed any consistent or specific evidence showing that pin-metered water lines are unable to support adequate preening for Pekin ducks.…”
Section: Discussionmentioning
confidence: 84%
“…The purpose of preening is to maintain feather quality and cleanliness in healthy birds. Our laboratory has examined and published observations of nearly 1,000,000 ducks raised with pin-metered water line systems; ducks observed in all our publications showed excellent body condition, particularly with eye and feather quality, and feather cleanliness regardless of other differences in management or environmental conditions (Fraley et al, 2013 ; Karcher et al, 2013 ; Campbell et al, 2014 ; Colton and Fraley, 2014 ; Rice et al, 2014 ; Campbell et al, 2015 ). Thus, we have not observed any consistent or specific evidence showing that pin-metered water lines are unable to support adequate preening for Pekin ducks.…”
Section: Discussionmentioning
confidence: 84%
“…For each repeated experiment, we rotated the light among the different pens to minimize any pen-location affects. All lights were from fluorescent bulbs and the photonic energy was normalized to 1.6 × 10 3 μM photons/m 2 /sec at the level of the ducks’ heads in each pen, as we have described previously (Campbell et al, 2015 ). Blood samples were collected from all drakes during the scotophase 1 h prior to light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Male quail appear to respond equally in testicular growth to either blue or full-spectrum white light (Nakane et al, 2010 ). Although in some species, blue light is sufficient and even desirable for increased growth, reproduction, or other favorable behaviors (Levenick and Leighton, 1988 ; Prayitno et al, 1997 ; Rozenboim et al, 2004 ; Iyilikci et al, 2009 ; Zhang et al, 2014 ), this condition does not appear to be the case for ducks (Campbell et al, 2015 ). It has been suggested that for optimal growth (Campbell et al, 2015 ) and reproductive development to occur in drakes, both red and blue wavelengths are required (Benoit, 1961 ; Benoit, 1964 ).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial illumination is widely used in the poultry industry, and both the optimum photoperiod and light wavelength have been investigated [ 1 , 2 ]. We previously showed that red light (RL) supplementation increases the laying rate of pigeons and alters the expression of the circadian gene BMAL1 [ 3 , 4 ], and another investigation performed in experimental rooms reached the similar conclusion that RL promotes pigeon egg production while blue light (BL) has the opposite effect [ 5 ].…”
Section: Introductionmentioning
confidence: 99%